Epicardial Adipose Tissue: Clinical Biomarker of Cardio-Metabolic Risk - Villasante Fricke, Alexandra C. (Int J Mol Sci, 2019)
Epicardial adipose tissue (EAT) is part of the visceral adipose tissue (VAT) that surrounds the heart and it is a quantifiable, modifiable, and multifaceted tissue that has both local and systemic effects. When EAT is enlarged, EAT contributes to atherosclerotic cardiovascular disease (ASCVD) risk and plays a role in the development of metabolic syndrome (MetS). In this review, we will discuss the role of EAT in various facets of MetS, including type 2 diabetes mellitus (T2DM) and insulin resistance. We examine the association between EAT and liver steatosis. We also address the correlations of EAT with HIV therapy and with psoriasis. We discuss racial differences in baseline EAT thickness. We conclude that EAT measurement serves as a powerful potential diagnostic tool in assessing cardiovascular and metabolic risk. Measurement of EAT is made less costly, more convenient, and yet accurate and reliable by transthoracic echocardiography. Furthermore, modification of EAT thickness has therapeutic implications for ASCVD, T2DM, and MetS.